(untitled) (Experimental biology, 2018)
This article is devoted to the identification of physiological and biochemical features of the influence of chromium and heavy metals (HM) on microalgae. The chromium-accumulating ability of some microalgae and influence of HM on the physiological-biochemical parameters of microalgae in monoculture and mixed cultures are shown. The allelopatic relationships of microalgae and their influence on the processes of chromium and HM absorption are considered Microalgae A. flos-aquae, A. arnoldii, N. linckia, C. paryethina actively absorb chromium from the culture medium are shown. The greatest absorption of chromium and HM occurs in microalgae cultures with positive allelopathic interference: A. flos-aquae, A. arnoldii, A. flos-aquae, N. linckia. In this article discusses the results of experiments with test-objects of different trophic levels. The unicellular algae is the most sensitive group of organisms to potassium dichromate that is shown. Particularly emphasized is the chromium accumulating capacity of certain plant objects, including microalgae. In studies on the effects of harmful substances on aquatic organisms, potassium dichromate is used as a reference toxicant. Their brief characteristics, pathways and migration, including intracellular and extracellular detoxification of HM ions, are given. The results of investigations are that physiological and biochemical processes of microalgae in conditions of environmental contamination with chromium ions have a general biological significance and can be used for the study of phytoremediation, ecological physiology and biotechnology. The data obtained in the research can be used to develop methods for biological treaHMent of wastewater and closed water systems contaminated with chromium.